Effects of Apigenin Treatment on Random Skin Flap Survival in Rats - Ma, Xinyi; Lin, Yuting; Liu, yingying; Li, Wenjie; He, Jibing; Fang, Miaojie; Lin, Dingsheng (Frontiers in Pharmacology, 2021)
Random skin flaps are often used in plastic surgery, but the complications of marginal flap ischemia and necrosis often limit their wider clinical application. Apigenin (Api) is a flavonoid found in various fruits and vegetables. Api has been shown to promote angiogenesis, as well as reduce oxidative stress, membrane damage, and inflammation. In this study, we assessed the effects of Api treatment on random skin flap survival. Dorsal McFarlane skin flaps were transplanted into rats, which were randomly divided into three groups: control (normal saline), low-dose Api (20 mg/kg), and high-dose Api (50 mg/kg). Seven days after the surgery, the activity of superoxide dismutase (SOD) and the level of malondialdehyde (MDA) were measured. Histological analyses were performed to determine flap survival and tissue edema. Hematoxylin and eosin (H&E) staining was performed to assess the histopathological changes in skin flaps, and the levels of microvascular density (MVD) were determined. Laser doppler flowmetry was used to assess microcirculation blood flow. Flap angiography was performed by injection of lead oxide/gelatin. The expression levels of vascular endothelial growth factor (VEGF), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and interlukin-1β (IL-lβ) were evaluated by immunohistochemistry. Rats in the high-dose Api group exhibited higher average flap survival area, microcirculatory flow, increased SOD activity, and higher VEGF expression levels compared with the other two groups. Furthermore, the levels of MDA and pro-inflammatory cytokines were significantly decreased in rats treated with high-dose Api. Our findings suggest the potential usefulness of Api in preventing skin flap tissue necrosis.